Seasonal and spatial characteristics of QPE errors over Indian region (MAUSAM, 2003)
The  study  examines the performance of INSAT derived quantitative precipitation estimates( QPE)  for different varying synoptic conditions and also presents  a quantitative assessment of spatial and seasonal characteristics  of these  errors  over  Indian  region making  detailed inter-comparison with  land rainfall observations. The  study  reveals that the  QPE, in general, is able to  capture rainfall pattern associated with different synoptic conditions  and  spatial distribution of mean rainfall of each season. But it has certain seasonal and spatial biases. The rainfall over most part of the country south of Lat. 30° N is under-estimated in all seasons except pre-monsoon.  For the  region north of Lat.  30 ° N where   western disturbances are dominant, rainfall is over estimated.  In the convective season of pre-monsoon, QPE has got very high degree of correspondence with the observed rainfall.